Functional morphology of digestive organs of newborn calves and pathogenesis of escherichiosis - S. M. Suleymanov (Ветеринария сегодня)
Despite numerous studies, the problem of escherichiosis in newborn calves remains one of the most urgent due to the extensive spread of the disease and high mortality of young animals. This paper presents results of experimental studies carried out at the FSBSI “All-Russian Veterinary Research Institute of Pathology, Pharmacology and Therapy”.T he aim of the work was to conduct complex morphological studies using modern methods for a deeper understanding of escherichiosis etiology and pathogenesis. For that, pathological samples were collected from 28 1–10 day-old calves diagnosed with colibacteriosis at the initial disease stage, demonstrating pronounced clinical signs and having the terminal stage of the disease. Samples from 6 clinically healthy calves of a similar age were used as control.It was found that newborn calves at the initial stage of escherichiosis demonstrated early structural changes in the ultrastructure of mucosa cells of the rennet and small intestine, as well as in the liver parenchyma, and mild changes – in the exocrine part of the pancreas. The most profound morphofunctional changes were observed in digestive organs with apparent clinical signs of the disease. As the condition developed, the range of pathological processes expanded and involved the structural organization of the rennet, small and large intestines, liver and pancreas. At the terminal stage of escherichiosis, deep inflammatory processes occurred not only in digestive organs, but also in other systems of diseased calves. Structural changes in digestive organs had an alterative nature at the initial disease stage, whereas in case of clinically pronounced disease signs there were manifestations of catarrhal-necrotic inflammation with multiple hemorrhages n the gastrointestinal tract and parenchymal organs. Digestive organ pathology plays the leading role in formation of the clinical and morphological picture at the initial stage of escherichiosis in calves. As the disease developed, the calves demonstrated changes at molecular and subcellular levels that were detected using histochemical and ultrastructural tests.